STUDI ETNOBOTANI TUMBUHAN SUB KELAS ROSIDAE DAN PENGGUNAANNYA SEBAGAI OBAT TRADISIONAL DI KECAMATAN BATURRADEN KABUPATEN BANYUMAS - Suparman, Suparman; Diniatik, Diniatik; Kusumaningrum, yah; Yulianto, Yulianto (Sainteks, 2012)
This study aims to know the medical plants of Rosidae sub class and Zingiberaceae family and the usage as a traditional medicine by people of Baturraden subdistrict, Banyumas regency. The method to be used was a qualitative approach by observation without participan. Observation was done to observe the knowledge of the indigenous peoples about medicinal plants. Data were collected by using semi-structured interview. Specimens were collected from the growing sites with the help of key informants. Analysis was done by two main approaches: medicinal etnobotany and chemotaxonomie. People used the medicinal plants for traditional healing. 22 species from 8 families of Rosidae sub class and 16 species from Zingiberaceae were reported to be used by them as medicines.Keywords: Ethnobotany, Baturraden Subdistrict, Rosidae sub class, Zingiberaceae